Autosomal recessive forms of hereditary motor and sensory neuropathy. Issue 8 (August 1980) - Harding, A E; Thomas, P K
Abstract : Six families are described with hereditary motor and sensory neuropathy (HMSN) of probable autosomal recessive inheritance. Four of these were classified as HMSN type I and two as type II. The consanguinity rate in this series was high, suggesting that these recessive genes are rare. In comparison with the dominantly inherited forms of these disorders, the mean age of onset was significantly earlier for the type II cases but did not differ for the type I patients. Motor nerve conduction velocity was significantly less for the type I cases but did not differ for the type II form. The recessive type I cases tended to show a greater incidence of weakness, ataxia, tendon areflexia and scoliosis than in the dominant form. The importance of differentiating such cases from Friedreich's ataxia is emphasised.